Comparative antioxidant study of stem and stem induced callus of Phyllanthus fraternus webster - An important antiviral and hepatoprotective plant - Upadhyay R.; Chaurasia J.K.; Tiwari K.N.; Singh K. (My University, 2025)
Phyllanthus fraternus is widely used in the cure of various liver diseases and possess antiviral properties especially against hepatitis virus. In the present study, evaluation of the antioxidant activity of stem and calli induced from stem has been done by different assays. Extraction was done by standard method in water and ethanol. Total antioxidant capacity was measured by 1, 1-diphenyl-2-picrylhydrazyl free radical scavenging method. Lipid peroxidation was measured in terms of thiobarbituric acid-reactive substances (TBARS) by using egg yolk homogenates as lipid-rich media, and superoxide radical scavenging activity was measured using riboflavin-light-nitro blue tetrazolium assay. Reducing power was determined on the basis of Fe3+-Fe 2+ transformation in the presence of the extract. In addition to the antioxidant activity, polyphenolic compounds like total phenolics and flavonoids were also measured by spectroscopic method. Results showed that the ethanolic extract of stem is more potent in antioxidant activity than its aqueous extract and ethanolic extract of calli. A significant correlation between antioxidant capacity and polyphenolic content and reducing potential was observed, indicating that phenolic compounds and reducers present in extract are major contributors to the antioxidant potential. Thus, this plant extract could be used as a potent natural antioxidant. © Springer Science+Business Media New York 2013.